2023
DOI: 10.31881/tlr.2023.001
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Water Consumption in Leather Processing and an Investigation of the Leather Quality

Abstract: Extensive use of water in different industries particularly leather tanning has drawn attention in recent years. In this research, a new approach has been developed to reduce water consumption in the tanning industry. Four different experiments were carried out on raw goat skins by using various quantities of water which were much lower than the influx of water consumed in the conventional leather tanning processes. One control experiment was conducted in which the volume of water was used as 100% of the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…According to earlier research, vegetable re-tanned leather shrank at 86.34 °C, which is much lower than the information from processed goat leather [39]. Other similar studies conducted by Yorgancioglu et al and Ferdous et al also reported the shrinkage temperature of chrome-tanned leather which was 103.5 °C [40] and 105 to 110 °C [41]. Interestingly, the shrinkage temperatures of all manufactured goat leather from the present study were considerably higher than the data reported previously in the literature [40][41][42] following the conventional method which demonstrated that the leather processed with recovered basic chromium salts was hydrothermally more stable.…”
Section: Hydrothermal Stability (Shrinkage Temperature)mentioning
confidence: 79%
“…According to earlier research, vegetable re-tanned leather shrank at 86.34 °C, which is much lower than the information from processed goat leather [39]. Other similar studies conducted by Yorgancioglu et al and Ferdous et al also reported the shrinkage temperature of chrome-tanned leather which was 103.5 °C [40] and 105 to 110 °C [41]. Interestingly, the shrinkage temperatures of all manufactured goat leather from the present study were considerably higher than the data reported previously in the literature [40][41][42] following the conventional method which demonstrated that the leather processed with recovered basic chromium salts was hydrothermally more stable.…”
Section: Hydrothermal Stability (Shrinkage Temperature)mentioning
confidence: 79%